SYMBOLIC SIGNS IN VISUAL ARTS - Mambetkadirova Durdana (American Journals Publishing, 2024)
This article also provides complete information about symbolic symbols in the visual arts, the history of its origin, logo, brand, icons
Keywords: Sign, shape, gesture, symbolism, evoke emotion, artwork